“Jogo Tonggo, Jogo Konco”: Community Adaptation Strategies During COVID-19 Pandemic in Central Java, Indonesia - Yuniati, Eka; Husain, Fadly; Husain, Fahrisal (Universitas Negeri Semarang, 2025)
The Covid-19 pandemic phenomenon has provided an extraordinary experience for the community. Many people have not been able to forget it, remember the incident as an unusual and frightening phenomenon. This study aims to understand the community's response and adaptation during Covid-19. Qualitative methods were chosen to frame this study, with data collecting techniques through interviews, observation and documentation. The study was conducted from May to June 2021, involving 41 informants from 14 different districts in Central Java. The results showed the responses emerged from the community were very diverse, both within the community and family. Handling of Covid-19 by the community is divided into the scope of self-isolation and isolation at home. The role of the community in handling residents affected is in the form of cooperation and caring for each other. In the family, each family member divides their role, both those who are sick and those who care for the sick. All elements or parties participate in the process of preventing and handling patients or family members exposed to Covid-19. In addition, the adaptation process was also carried out both in social life and in the workplace, for instance avoiding public activities and working from home.